Textural Insights Into the Evolving Lava Dome Cycles at Santiaguito Lava Dome, Guatemala - Rhodes, Emma; Kennedy, Ben M.; Lavallée, Yan; Hornby, Adrian; Edwards, Matt; Chigna, Gustavo (Frontiers in Earth Science, 2018)
The structures and textures preserved in lava domes reflect underlying magmatic and eruptive processes, and may provide evidence of how eruptions initiate and evolve. This study explores the remarkable cycles in lava extrusion style produced between 1922 and 2012 at the Santiaguito lava dome complex, Guatemala. By combining an examination of eruptive lava morphologies and textures with a review of historical records, we aim to constrain the processes responsible for the range of erupted lava type and morphologies. The Santiaguito lava dome complex is divided into four domes (El Caliente, La Mitad, El Monje, El Brujo), containing a range of proximal structures (e.g. spines) from which a series of structurally contrasting lava flows originate. Vesicular lava flows (with a’a like, yet non-brecciated flow top) have the highest porosity with interconnected spheroidal pores and may transition into blocky lava flows. Blocky lava flows are high volume and texturally variable with dense zones of small tubular aligned pore networks and more porous zones of spheroidal shaped pores. Spines are dense and low volume and contain small skeletal shaped pores, and subvertical zones of sigmoidal pores. We attribute the observed differences in pore shapes to reflect shallow inflation, deflation, flattening or shearing of the pore fraction. Effusion rate and duration of the eruption define the amount of time available for heating or cooling, degassing and outgassing prior to and during extrusion, driving changes in pore textures and lava type. Our new textural data when reviewed with all the other published data allows cyclic models to be developed. The cyclic eruption models are influenced by viscosity changes resulting from (1) initial magmatic composition and temperature, and (2) effusion rate which in turn affects degassing, outgassing and cooling time in the conduit. Each lava type presents a unique set of hazards and understanding the morphologies and dome progression is useful in hazard forecasting.